2014
DOI: 10.1186/2110-5820-4-10
|View full text |Cite
|
Sign up to set email alerts
|

Significant changes in the practice of chest radiography in Dutch intensive care units: a web-based survey

Abstract: BackgroundICU patients frequently undergo chest radiographs (CXRs). The diagnostic and therapeutic efficacy of routine CXRs are now known to be low, but the discussion regarding specific indications for CXRs in critically ill patients and the safety of abandoning routine CXRs is still ongoing. We performed a survey of Dutch intensivists on the current practice of chest radiography in their departments.MethodsWeb-based questionnaires, containing questions regarding ICU characteristics, ICU patients, daily CXR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
11
0
2
Order By: Relevance
“…[29][30][31][32] Despite these findings, our recent web survey of Dutch intensivists revealed that the strategy of daily routine CXRs is a rare practice nowadays, with the exception of routine CXRs for postoperative cardiac surgery patients. 33 Abandoning routine CXRs after cardiac surgery may be safe only when patients at risk are identified and certain indications for CXRs are stated.…”
Section: See Editorial Commentary Page 230mentioning
confidence: 99%
“…[29][30][31][32] Despite these findings, our recent web survey of Dutch intensivists revealed that the strategy of daily routine CXRs is a rare practice nowadays, with the exception of routine CXRs for postoperative cardiac surgery patients. 33 Abandoning routine CXRs after cardiac surgery may be safe only when patients at risk are identified and certain indications for CXRs are stated.…”
Section: See Editorial Commentary Page 230mentioning
confidence: 99%
“…Secondly, the prevalence of ‘on-demand’ prescription (88%) could be another reason for the lower frequency of CXR prescription in admitted patients. Several centres have reported a change in practice from routine CXRs to on-demand prescriptions over the past two decades [ 13 15 ] Although a prospective study conducted in multi-institutional PICUs suggested routine CXRs to be useful in a cohort of critically ill children, subsequent randomized controlled trials in adults and consensus opinions strongly supported the adoption of on-demand strategy to minimize the use of radiography in mechanically ventilated patients without compromising quality of care or safety [ 3 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Choosing Wisely campaign (2012) recommended not to use diagnostic tests including CXR on daily basis as they added no benefit to patient care besides increasing cost and potential harm [ 9 11 ]. Currently, though most intensivists prefer an on-demand strategy, a wide variation in practice has been reported across hospitals caring for adults and at some places, the daily routine CXR is still common [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two surveys from Dutch ICUs in 2005 and 2013 with different response rates found a decrease from 63% to 7% of ICUs reporting the use of routine daily CXRs. 26 , 27 To our knowledge, there are no studies of practice in the United States to evaluate the use of routine daily CXRs.…”
Section: Introductionmentioning
confidence: 99%